Pemikiran Ekonomi Islam Pada Masa Imam Al Ghazali (405-505H) - Utami, Rizky Ananda; Arif, Muhammad (Universitas Labuhanbatu, 2024)
The extensive and profound thoughts of Imam Al-Ghazali in the realms of Islamic spirituality and philosophy have enriched the understanding of various facets of life, including economic principles. This research aims to explore the foundations of Islamic economic thought according to Imam Al-Ghazali in his monumental works. The study focuses on analyzing economic concepts reflected in Al-Ghazali's works, such as